PERJALANAN MENUJU PEMAHAMAN YANG MENDALAM MENGENAI ILMU PENGETAHUAN: STUDI FILSAFAT TENTANG SIFAT REALITAS - Arif Rahman; Dase Erwin Juansah; Lukman Nulhakim; Basuki Basuki (LPPM Institut Pendidikan Nusantara Global, 2023)
The understanding of the philosophy of reality can vary from individual to individual. This is due to the different backgrounds, interests, approaches, and points of view that each person has about the subject. The philosophy of the nature of reality involves complex and abstract philosophical questions that can be interpreted and understood in different ways by different people. The aim of this study is to discuss the philosophy of reality as a journey towards a deeper understanding of science. This study is a qualitative descriptive study based on literature. The results of this research suggest that the journey towards a deeper understanding of reality involves an understanding of the nature of science itself, how science is acquired, and how science depicts reality. An in-depth understanding of reality can be gained by studying the history of philosophy, studying philosophical currents, reading classical and contemporary philosopher texts, engaging in discussions and debates, thinking critically and analyzing arguments, researching related disciplines, asking questions, and staying open.